Effects of Health Promoting Program on Health Behaviors among the Elderly Persons, Nonthaburi Province - Noiwat, Orawan; Prasertchai, Araya (Ratchaphruek Journal, 2015)
The purpose of this quasi-experimental research was designed to examine the effects of health promoting program applying self-efficacy theory on health behaviors among the elderly persons, Nonthaburi province. The sample was a member of an elderly club by using simple random method. Thirty elderly persons from Tambol Bangpood club and thirty elderly persons from Tambol Bantalat club were assigned to experiment and comparison groups respectively. The experimental group received a health promoting program that includes knowledge, perceived self-efficacy and outcome expectation. A health behavior included food consumption, exercise, stress management and dental health care. The instrument was a questionnaire and a test of knowledge. The statistics used to analyze the research data were percentage, mean, standard deviation, paired t-test and independent t-test. The results showed that; 1. The levels of knowledge, perceptions and expectations of elderly people before and after the health promotion program were different at the .05levelof significance. 2. Posttest of the experimental elderly group participating in the health promotion program showed an average score of health behaviors which was higher than before the experiment at the .05 level of significance. 3. Posttest of the experimental elderly group participating in the health promotion program had an average score of health behaviors higher than those who did not attend the program, at the .05 level of significance.